THE EFFECT OF HIGH PERFORMANCE WORK SYSTEMS ON EMPLOYEE PERFORMANCE WITH WORK ENGAGEMENT AS A MODERATING VARIABLE - Dasep Suryanto; Eva Desemberianita; Sugiarti; Djunaedi; Ilham Akbar (Adisam Publisher, 2024)
This research is a quantitative study with an explanatory approach, namely an approach that only relies on previous similar studies as a starting point to find elements of novelty in the research being conducted. The data used in this article is primary data that researchers obtained from the results of distributing questionnaires to 300 PT employees KAI spread throughout Indonesia. The questionnaire contains statements of agree, strongly agree, normal/so-so, disagree, and strongly disagree. The data obtained were analyzed using the smart PLS 4.0 analysis tool. that each variable used in this study has been successfully proven and accepted. This is because the first row of the third table of the Path Coefficients above has a positive relationship direction and a significant influence because it is below the significance level of 0.05, namely 0.035. This is because the higher the performance of the Work System, the easier it is for employees to complete their work. In addition, the next row of the third table of the Path Coefficients above also shows the same intent and purpose where the P-Values are positive and also below the significance level of 0.05, namely 0.007. This is because the more often employees are involved in a job, the more employees become accustomed to challenges and can continue to evaluate themselves so that the results of their work can be better over time. Thus it can be concluded that the first and second hypotheses in this article can be proven and accepted.